(untitled) (Perspectivas de las Ciencias Económicas y Jurídicas, 2019)
The discipline Introduction to Law has a long history in the scientific and pedagogical tradition of the Faculties of Law and its importance has grown over the years" (Martínez Paz, 2003: 25).Its name and structure were changed to adapt to the transformations of society, legal culture, the development of the science of law and the needs of university pedagogy.Assessing the contributions that have been made in the structuring of the subject, it is necessary to offer a new approach to define the theoretical and methodological problems.The subject is conceived as an introductory subject, not to the study of law or career, but to the law itself.The teaching of law is key in any change project for legal training, hence it is necessary to assess the importance of the task in the classroom and the daily actions and proposals.Consequently, both our proposal and the method is constructivist.